Hidden Harms of Hypnotics: a population based record linkage study of psychotropic medication and suicide risk - Ifeoma Onyeka; Aideen Maguire; Dermot O’Reilly (International Journal of Population Data Science, 2019)
Background/Main Aim Although psychotropic medication is a known risk factor for suicide, studies investigating the relationship between specific types of psychotropic medication and suicide in adults are scarce.